2022
DOI: 10.2147/ijn.s362244
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber-Derived Nanovesicles Containing Cucurbitacin B for Non-Small Cell Lung Cancer Therapy

Abstract: Purpose In recent years, a variety of nanoparticles with excellent anticancer and delivery properties have emerged for cancer therapy. However, potential toxicity, high production cost and complex preparation procedures have been obstacles to their use in biomedicine. Here, we obtained cucumber-derived nanovesicles (CDNVs) at high yield and low cost by simple juicing and ultracentrifugation. The anticancer effects of CDNVs were evaluated in vitro and in vivo. Methods Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Furthermore, the consumption of certain naturally derived dietary products at high levels may decrease the likelihood of tumor recurrence and enhance survival in breast cancer patients [73]. Many nutritional natural products found in the Mediterranean area, including pomegranate [74,75], edible mushrooms [76,77], marine algae [78,79], curcumin [80,81], whole-grain cereals [82,83], citrus fruit [84,85], grapes [86,87], and cucumber [88,89], have been shown in experimental studies to disrupt the development and progression of cancer via the application of anticancer or antineoplastic activity.…”
Section: Fruits Vegetables and Plant-based Foodsmentioning
confidence: 99%
“…Furthermore, the consumption of certain naturally derived dietary products at high levels may decrease the likelihood of tumor recurrence and enhance survival in breast cancer patients [73]. Many nutritional natural products found in the Mediterranean area, including pomegranate [74,75], edible mushrooms [76,77], marine algae [78,79], curcumin [80,81], whole-grain cereals [82,83], citrus fruit [84,85], grapes [86,87], and cucumber [88,89], have been shown in experimental studies to disrupt the development and progression of cancer via the application of anticancer or antineoplastic activity.…”
Section: Fruits Vegetables and Plant-based Foodsmentioning
confidence: 99%
“… HGC-27; HepG2; MDAMB-231 Inhibited the proliferation of human non-small cell lung cancer cells by inhibiting signal transduction and activation of transcriptional activator 3, generating ROS, promoting cell cycle arrest and activating the caspase pathway. [ 50 ] Sage Pro-apoptotic Differential ultracentrifugation NTA – MIA PaCa-2, MCF-7 – [ 51 ] Artemisia Anti-inflammatory Differential ultracentrifugation; density-gradient centrifugation. BCA protein assay kits ADNVs (25 mg/kg), administered alone or in combination with αPD-L1 antibody (10 mg/kg), were administered by instillation on day 7 following inoculation of tumor cells, with subsequent doses given every 3 days for a duration of 2 weeks.…”
Section: Bioactivity: Pdnvs As An Anti-tumor Therapeuticmentioning
confidence: 99%
“…Chen’s group found that centrifugation times of 20 minutes and at lower centrifugation speeds increased the yield of NVs while avoiding aggregation. 50 , 85 The use of buffers containing polyethylene glycol can maintain the integrity of NVs by wrapping them up to form a mesh network. Centrifugation methods based on polyethylene glycol-6000 (PEG6000) can also greatly improve the yield of NVs, with the authors indicating that 60–90% of ginger-derived NVs can be collected.…”
Section: Key Consideration Of Pdnvs As Anti-tumor Toolsmentioning
confidence: 99%
“…Chen et al obtained cucumber-derived nanovesicles (CsDNVs) at high yield and low cost, which may be natural nanocarriers that contain Cucurbitacin B (CuB, STAT3 inhibitor). They demonstrated that these CsDNVs enhanced the anti-cancer effects of CuB by improving its bioavailability [119]. Notably, owing to the remarkable capability for penetration of the BBB, exosomes might improve the prognosis of glioblastoma (GBM).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%